2011
DOI: 10.1002/app.34629
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photoinitiating activity study of polymeric photoinitiators bearing BP moiety based on hyperbranched poly(ester‐amine) via thiol‐ene click reaction

Abstract: A series of polymeric photoinitiators (BPHPEAs) bearing BP moiety based on hyperbranched poly(ester-amine) were synthesized via the thiol-ene click reaction of 3-(4-benzoylphenoxy)propyl 2-mercaptoacetate (BPPM) with acrylated HPEA. BPPM was obtained by the esterification of (4-(3-hydroxypropoxy) phenyl) phenyl methanone (HPPM) with mercaptoacetic acid in the presence of p-toluene sulphonic acid as a catalyst. HPEA was prepared through Michael addition of piperazine with tri(hydroxymethyl)propane triacrylate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Interestingly, the polymeric species exhibited excellent absorption characteristics compared to benzophenone and was shown to have higher initiator efficiency in the subsequent polymerisation of HDDA. In a similar vein, Xie et al 33,34 reported two examples of benzophenone-based polymeric photoinitiators based on hyperbranched poly(ester-amine) and poly(ester/ ether) (P1000). In both instances the preparation of the polymeric photoinitiators involved a thiol-Michael reaction between appropriate functional species.…”
Section: New Practical Considerationsmentioning
confidence: 94%
“…Interestingly, the polymeric species exhibited excellent absorption characteristics compared to benzophenone and was shown to have higher initiator efficiency in the subsequent polymerisation of HDDA. In a similar vein, Xie et al 33,34 reported two examples of benzophenone-based polymeric photoinitiators based on hyperbranched poly(ester-amine) and poly(ester/ ether) (P1000). In both instances the preparation of the polymeric photoinitiators involved a thiol-Michael reaction between appropriate functional species.…”
Section: New Practical Considerationsmentioning
confidence: 94%
“…These two moieties were coupled via hydrosilylation of the hyperbranched organosilane (Scheme A red-shifted UV absorption in the HCPPI products was observed due to the introduction of alkyl. Xie et al [40] designed an A2B3 monomer system for the synthesis of hyperbranched polymer, which contains hydrogen donor for the Type-II PIs located on the terminal groups.…”
Section: Hyperbranched and Cross-linked Polymeric Photoinitiators (Hc...mentioning
confidence: 99%
“…Therefore in recent years, polymerizable [5][6][7][8][9][10][11][12][13][14][15], oligomeric or polymeric photoinitiators (PPIs) [16][17][18][19][20][21][22][23] meeting most of the above mentioned requirements received continued interest due to their advantages in comparison with their corresponding low molecular weight non-monomeric analogs. The photoinitators derived from dendrimers and hyperbranched polymers were reported for their high functionality and low viscosity compared to linear polymers [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%